(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The GRT DW/BIDevelopment Approach is a comprehensive approach to the design, development,and implementation of data warehouse solutions. It is based on input fromseveral sources and from the direct experience of the GRT Consulting.